INFORMATION AND COMMUNICATION TECHNOLOGIES AS MEDIATORS OF LEARNING: CURRENT CHALLENGES - Felipa Andrade, Rossana Fiorella (2020)
Learning and different ways of learning have always been the subjetc of concern and research in the educational field. The presence of information and communication technologies (ICT) and its insertion in the teaching-learning processes have resulted in the creation of new learning theories, such as Connectivism, and, simultaneously, the generation of various challenges, both for educational institutions and for teachers and students. In this article, we try to describe the relationship between technology and education, based on the review of their development areas and the identification of the main challenges currently facing classrooms.